Program Penghijauan sebagai Bentuk Kepedulian Terhadap Lingkungan - Hendriana Liwun; Maria I. Bria; Maria D. Fallo; Oktaviana Suriani; Yakobus Beraheng; Noviana Dosantos; Gracianus Edwin Tue. P. Lejap (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2024)
Concern for the environment is the responsibility of all parties, both the community, government and related parties. Greening activities are activities to maintain a good environment and provide a good impression of health, beauty and prosperity. Greening activities are carried out using participatory methods involving students and the school. The results of this activity illustrate that this program is not only successful in utilizing abandoned land or making the environment more beautiful, but also successfully increasing the ties of friendship between students and all important elements in the school. The design of the program activities and efforts that have been made by students are expected to provide maximum benefits to the community in the school environment.